2022
DOI: 10.33558/bentang.v10i2.3263
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kerusakan Struktur Bangunan dan Manajemen Bencana Akibat Gempa Bumi, Tsunami, dan Likuifaksi di Palu

Abstract: Strong column-weak beam merupakan konsep desain yang perlu diterapkan dan diperhatikan dalam perencanaan struktur gedung (gedung bertingkat tinggi dan gedung bertingkat rendah). Umumnya kegagalan struktur terjadi pada sambungan balok-kolom (beam-column joint). Kegagalan tersebut terjadi karena kurangnya perhatian terhadap konsep desain yang baik dan benar. Detailing pembesian pada kolom, balok, dan sambungan balok-kolom masih belum secara penuh menerapkan standard SNI-2847-2019 yang mengakibatkan tulangan tida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Indo-Australia Tectonic plates observed to move 6-14 cm per year, this tectonic activity become the main reason of the high intensity earthquake which happen either in the land or the sea as the triggered of Tsunami. This phenomenon proofed as the reason of the Tsunami which happened previously such as: Tsunami Aceh (2004), Tsunami Nias (2005), and Tsunami Mentawai (2010) [12], [13]. Krakatau Volcanic Mountain, one of the volcanic mountains under high observation of BMKG (Metrological, Seismicity, and Geophysical Bureau, Indonesia) located in Lampung, beside the tectonic activity due to the plate movement, but also the volcanic activity of the Krakatau Mountain caused Lampung become one of the provinces with the high seismicity region.…”
Section: Introductionsupporting
confidence: 60%
“…Indo-Australia Tectonic plates observed to move 6-14 cm per year, this tectonic activity become the main reason of the high intensity earthquake which happen either in the land or the sea as the triggered of Tsunami. This phenomenon proofed as the reason of the Tsunami which happened previously such as: Tsunami Aceh (2004), Tsunami Nias (2005), and Tsunami Mentawai (2010) [12], [13]. Krakatau Volcanic Mountain, one of the volcanic mountains under high observation of BMKG (Metrological, Seismicity, and Geophysical Bureau, Indonesia) located in Lampung, beside the tectonic activity due to the plate movement, but also the volcanic activity of the Krakatau Mountain caused Lampung become one of the provinces with the high seismicity region.…”
Section: Introductionsupporting
confidence: 60%
“…Palu memiliki sejarah namanya melalui kata Topalue yang berarti daratan yang terangkat, karena pada mulanya wilayah tersebut merupakan sebuah lautan, akibat adanya gempa bumi dan pergerakan lempeng tektonik (palu koro), dengan demikian daerah terdahulunya yang merupakan lautan menjadi naik dan terbentuk sebuah daratan yang mana sekarang dikenal sebagai kota Palu. Palu sendiri merupakan satu diantara kota yang terkena dampak bencana tsunami, gempa, serta likuifaksi tepatnya 28 September 2018 lalu [3].…”
Section: Pendahuluanunclassified
“…Soil experiencing liquefaction undergoes a transformation from a solid to a liquid-like state Instances of liquefaction have occurred in various countries, resulting in significant destruction and loss of life. An example of liquefaction is the event that took place in Palu, North Sulawesi, Indonesia, in 2018 [3]. The Indonesian National Board for Disaster Management (BNPB) reported that the earthquake and liquefaction event in Palu led to 2,034 casualties, 671 people missing, and 152 people being buried alive [4].…”
Section: Introductionmentioning
confidence: 99%